VIRTUAL HUB FOR SMALL MEDIUM ENTERPRISES (SMES) IN INDONESIA AND MALAYSIA (POSH COSH AND HERBAL PRODUCT CASES) - Huda Ibrahim; Suwannit Chareen Chit; Irma Rachmawati (International Journal of Latin Notary, 2021)
ASEAN countries are a melting pot of 617 million people with rich culture and unique skills and can only be found in this part of the world. Over the decades, this region had seen immense transformation due to the economic boom but still retained its historical identity. It is no wonder that one can see a blend of modern sophistication and traditional lifestyle existing side-by-side in ASEAN Countries today. Small Medium Enterprises (SMEs) are integral to the ASEAN Member States' economic development and growth. They vastly outnumber larger enterprises in both the number of establishments and share of the labor force they employ. The result of this hub requires active participation by multiple stakeholders, particularly the entrepreneurs. Therefore, their views are valuable to us and will be taken into consideration. It is hoped that the principles of openness, user-centricity, and stakeholder participation are upheld.